LEGAL PROTECTION EFFORTS AGAINST MINORS IN NARCOTICS CRIMES - Fadillah Aditya Prtama; Ismaidar (Universitas Efarina, 2023)
Children are the future of the nation. Because they are the future of the nation, children need to receive special attention for their growth and development towards good and dignified maturity. 18 years is the determining age limit for minors according to criminal law and 21 years according to civil law. At this age, children tend to always want to commit deviant acts. For example, engaging in promiscuity, trying to drink alcohol, and even trying to use other prohibited substances such as narcotics. The government is responsible for legally protecting these children if unlawful actions occur, including if they use narcotics. The method used in this writing is a qualitative method with a juridical-normative approach, which refers to juridical sources which will focus on Law Number 35 of 2009 concerning Narcotics, Law Number 11 of 2012 concerning the Juvenile Criminal System, and Law-Law Number 23 of 2002 concerning Child Protection. The results of the research show the benchmarks for determining the age of minors according to law and the forms of legal protection that can be applied to minors in narcotics crimes. First, the Position and Age of Children in Legislation according to Law no. 1/1974 concerning Marriage, namely 19 years for men and 16 years for women. According to Law no. 3/1997 concerning Juvenile Justice, namely that they have reached the age of 8 (eight) years but have not yet reached the age of 18 (eighteen) years and have never been married. According to Law no. 4/1979 about